METODE GURU DALAM MENGENALKAN ILMU TAUHID UNTUK ANAK USIA DINI DI TK DHARMA WANITA TAMPUS UJUNGGADING KEC LEMBAH MELINTANG KAB. PASAMAN BARAT - Ruki'ah; Arman Husni; Iswantir M; Wedra Aprison (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by events that occur in the field, that researchers see that early childhood does not understand in terms of knowing the child who is God when asked by the teacher, the teacher does not understand the method that should be set in school in learning monotheism so that early childhood do not understand what the teacher is saying. This study uses a qualitative descriptive method, which describes the events that occur in the field as they are. The data collection that the researcher did was by observation and interviews. Research informants consist of key informants and supporting informants, key informants are Dharma Wanita Kindergarten teachers, while supporting informants are Dharma Wanita Kindergarten students. Data were analyzed by data collection techniques, data processing techniques, and data triangulation. Based on research conducted by researchers regarding the